How are problem-solving skills equipped in learning biodiversity? The efforts to realize learning of society 5.0 - Ulfi Faizah; Nuryani Yogipranata Rustaman; Yayan Sanjaya; Ana Ratna Wulan; Reni Ambarwati; Dwi Anggorowati Rahayu (Biosfer: Jurnal Pendidikan Biologi, 2022)
Problem-solving skills and the ability to live sustainably by maintaining the harmonization of the environment/biodiversity are some of the characteristics of Society 5.0. Efforts to apply these characteristics need to be realized in biodiversity studies at universities. Currently, information about these efforts needs to be reviewed to develop efforts to equip skills which directly useful to solve problems in society. The study's aim described various efforts to equip problem-solving skills in biodiversity learning to realize learning of Society 5.0. The research method was descriptive and the respondents were lecturers who teach biodiversity subjects (n = 82) at various colleges in Indonesia (n = 38). The instrument was a questionnaire in Google form that contained questions about problem-solving skills. The data were analysed descriptively using Microsoft Excel version 2019. The results showed 98.8% of respondents had equipped problem-solving skills to their students. Regarding new literacy, 68.3% of respondents said they know and apply it in many ways in lecture activities. The conclusion This study concluded that various efforts had been made in biodiversity learning in colleges in equipping problem-solving skills as learning society 5.0. Lecturers need to increase skills of new literacy that support the implementation of learning of society 5.0. In the future, problem solving skills by integrating new literacy can become a necessity to be applied in more various universities.